Analisis Pemangku Kepentingan dalam Pengembangan Energi Terbarukan: Studi Kasus Pembangkit Listrik Tenaga Surya (PLTS) Desa Muara Enggelam - Adhityo Nugraha Barsei; Joko Saptohadi (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
Muara Enggelam Village is located in Kutai Kartanegara Regency, East Kalimantan Province. Limited access to electricity makes it difficult for rural communities to carry out their economic activities. The abundant potential of solar resources has encouraged the Kutai Kartanegara Regency Government through the Ministry of Energy and Mineral Resources (ESDM) to develop Renewable Energy (EBT). With these efforts, Muara Enggelam Village can benefit from low-cost electricity from a solar power plant (PLTS) who managed by BUMDes